2023
DOI: 10.3390/pr11061838
|View full text |Cite
|
Sign up to set email alerts
|

Improved Active Islanding Detection Technique with Different Current Injection Waveform

Abstract: The active frequency drift (AFD) method is an effective method to detect islanding in grid-connected photovoltaic systems. However, it has some inherent drawbacks, such as generating higher harmonics. In order to reduce the harmonics and non-detection zone (NDZ), various improved AFD methods have been proposed, but they still suffer from high harmonics and reduced detection speed. To overcome these limitations, this paper proposes an innovative islanding detection technique based on AFD. Analysis reveals that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…These can be subdivided into passive or active, depending on the operating hypothesis they employ [29]. Active IDMs continuously introduce perturbations at the PCC and assess the effect of these perturbations on the electric variables [30,31]. The central hypothesis behind active IDMs is that the introduced perturbation can be negligible when a DG is connected to the main grid but significantly affects sensed variables when an unintentional island is formed.…”
Section: Literature Review Of Islanding Detection Methodsmentioning
confidence: 99%
“…These can be subdivided into passive or active, depending on the operating hypothesis they employ [29]. Active IDMs continuously introduce perturbations at the PCC and assess the effect of these perturbations on the electric variables [30,31]. The central hypothesis behind active IDMs is that the introduced perturbation can be negligible when a DG is connected to the main grid but significantly affects sensed variables when an unintentional island is formed.…”
Section: Literature Review Of Islanding Detection Methodsmentioning
confidence: 99%
“…Liu et al [5] selected 31 manufacturing industries, used the stochastic frontier analysis (SFA) method to measure R&D efficiency, and used the Tobit regression method to examine the relationship between direct government subsidies, preferential tax policies and manufacturing R&D efficiency. An innovative islanding detection technique was proposed based on active frequency drift (AFD) and the analysis revealed that the proposed method reduced harmonics by 68% compared to conventional AFD and had a larger chopping factor [6]. A technology with a manufacturing working environment extending underwater was proposed for lowering the cost of installing new submarine pipelines, polluting the ocean less, and improving recycling efficiency [7].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from this, significant load shedding can provoke over-voltages and may even imply voltage instability [3]. Furthermore, harmonics, resonances, switching operations and faults may lead to the amplification of voltage levels due to non-linear loads, power electronic devices, insulation failures or ground faults, among others [4][5][6].…”
Section: Introductionmentioning
confidence: 99%